Perceptions of Secondhand and Thirdhand Smoke Among Hispanic Residents of Multiunit Housing - Rendón, Angélica Delgado (J Immigr Minor Health, 2017)
Despite the progressive adoption of smoking bans in public spaces, children living in multi-unit housing remain at risk of exposure to secondhand smoke (SHS) and thirdhand smoke (THS). Hispanic populations in California are particularly vulnerable to the harmful effects of SHS and THS because a large proportion of Hispanics live in multi-unit housing. Three focus groups were conducted in the fall of 2012 (in Spanish and English, N = 24) to understand Hispanics’ knowledge of and experiences with SHS and THS, including barriers to avoiding smoke exposure and strategies for protecting their homes from smoke. Hispanic residents reported unpleasant experiences with SHS and THS and were generally knowledgeable about the adverse health effects, although they were not familiar with the term “thirdhand smoke.” Some participants also mentioned marijuana smoke as a potential health hazard. Hispanic cultural values made participants reluctant to confront their neighbors but also motivated them to find ways to protect their families from smoke. Potential solutions included working with the smokers to designate a smoking area and gaining support from the building owners. Broad smoking policies should be implemented to help Hispanic residents overcome cultural and social barriers to smoke free air.